Effect of the Target and Conflicting Frequency and Time Ranges on Consonant Enhancement in Normal-Hearing Listeners - Yoon, Yang-Soo (Frontiers in Psychology, 2021)
We determined the effects of intensifying useful frequency and time regions (target frequency and time ranges) and removing detrimental frequency and time regions (conflicting frequency and time ranges) for consonant enhancement. Thirteen normal-hearing listeners participated in two experiments. In the first experiment, we identified target and conflicting frequency and time ranges for each consonant under a quiet, dichotic listening condition by analyzing consonant confusion matrices. The target frequency range was defined as the frequency range that provided the highest performance and decreased 40% from the peak performance from both high- and low-pass filtering schemes. The conflicting frequency range was defined as the frequency range that yielded the peak errors of the most confused consonants and 20% less than the peak error from both filtering schemes. The target time range was defined as a consonant segment that provided the highest performance and decreased 40% from that peak performance when the duration of the consonant was systematically truncated from the onset. The conflicting time ranges were defined on the coincided target time range because, if they temporarily coincide, the conflicting frequency ranges would be the most detrimental factor affecting the target frequency ranges. In the second experiment, consonant recognition was binaurally measured in noise under three signal processing conditions: unprocessed, intensified target ranges by 6 dB gain (target), and combined intensified target and removed conflicting ranges (target-conflicting). Results showed that consonant recognition improved significantly with the target condition but greatly deteriorated with the target-conflicting condition. The target condition helped transmit voicing and manner cues, while the target-conflicting condition limited the transmission of these cues. Confusion analyses showed that the effect of the signal processing on consonant improvement was consonant-specific: the unprocessed condition was the best for /da, pa, ma, sa/; the target condition was the best for /ga, fa, va, za, ʒa/; and the target-conflicting condition was the best for /na, ʃa/. Perception of /ba, ta, ka/ was independent of the signal processing. The results suggest that enhancing the target ranges is an efficient way to improve consonant recognition, while removing conflicting ranges negatively impacts consonant recognition.